The struggling readers’ perceptions on the intensive reading programme / Jasvini Narayanan Athinarayanan - Jasvini Narayanan , Athinarayanan (2019)
This study investigated the effects of a ten-week Intensive Reading programme on struggling readers following a usability perspective design. The purpose of this study is to examine the effects of the ten- week Intensive Reading Programme designed to provide extra coaching for struggling readers. The ten weeks IRP covered various aspects of literacy teaching such as phonics rules, phonetic word test, sight words, paragraph reading, organizing story map, comprehending text. In this study, four reading strategies were being used by the struggling readers in the IRP, and they are: reading aloud, silent reading, cooperative reading and oral reading. The study addresses two major questions. The first examined the struggling readers’ perspective of IRP. The second one investigates if there is any significant difference in using Intensive Reading Programme on students reading comprehension of struggling readers. A total number of 32 primary school students from Sri Mawar private school, Johor Bahru, 17 males and 15 females were involved. They were put into two groups for monitoring purpose. A quantitative analysis was used to examine the effects of the IRP on struggling readers. Data was gathered through questionnaire and this supports the first research question. This questionnaire was framed as per the Summer Literacy Program Participant Survey and Questionnaire which was designed by Haug (2010). The Reading Assessment Tests were the grade three paper, designed by Sri Mawar International English Subject teachers. The findings revealed that IRP was successful as the survey results showed a majority of participants felt the positive effects of the IRP on comfort and confidence levels. Besides that, students’ reading assessment results indicated a significant increase in scores for the population from reading assessment tests. Therefore, this study could be used as a guide as reading programme developers can see how the pupils’ have improved in their reading abilities from the data collected.